Previous Archaeological Excavations along the 'Ostlänken' Railway Corridor 1965:2012: Klinga - a grave field - Swedish National Heritage Board, UV Öst (Uppsala University, 2017)
A preliminary investigation of the site was carried out in 1988. Since the area was covered by dense forest, only smaller areas could be investigated. A trench was excavated in the area where a number of remains were known to be located, as well as a small area to the south west. The excavations revealed a hearth and stone remains. the latter were later interpreted as being of natural origins. No new graves were discovered in the course of this investigation.

Prior to the principal investigation, the road area was cleared of forest and other surface material. The principal investigation revealed remains over an area of 10 000 m².

The ZIP-file contains one Shapefile with information on trenches, ancient monuments and other data from the archaeological survey, as well as a geo-referenced map (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

Under säsongen 1988 genomfördes en förundersökning på platsen. Då området var bevuxet med tät skog kunde inga större ytor avtorvas. Schakten grävdes i anslutning till de kända stensättningarna samt på en yta sydost om dessa. I schakten påträffades en härd och två stenpackningar. Stenpackningarna tolkades som eventuellt naturliga. Det upptäcktes inga nya gravar vid förundersökningen.

Inför slutundersökningen röjdes vägområdet. Iakttagelser efter skogsavverkningen förebådade ett mycket större fornlämningsområde än vad förundersökningen visat. Undersökningen omfattade till slut ett fornlämningsområde om ca 10 000 m².

ZIP-filen innehåller data i form av fyra shapefiler med information om eventuella schakt, påträffade forn- och kulturlämningar samt andra metadata från den arkeologiska utredningen, samt en georefererad karta (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Klinga - ett gravfält
Keywords: finds; fynd; HISTORY; HISTORIA; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive